MODEL PERHITUNGAN UNIT COST LAYANAN KESEHATAN DENGAN METODE BIAYA KONVENSIONAL DAN ABC (STUDI KASUS DI PUSKESMAS â€œXâ€ KABUPATEN LUMAJANG) - Mulyono, Imam (Prodi Akuntansi FEB UNITOMO, 2017)
@font-face font-family: "Times New Roman"; @font-face font-family: "å®‹ä½“"; @font-face font-family: "SimSun"; p.MsoNormal margin: 0pt 0pt 0.0001pt; text-align: center; font-family: "Times New Roman"; p.MsoFooter margin: 0pt 0pt 0.0001pt; text-align: center; font-family: "Times New Roman"; span.msoIns text-decoration: underline; color: blue; span.msoDel text-decoration: line-through; color: red; div.Section0 PublicÂ HealthÂ CenterÂ (PHC)Â isÂ oneÂ organizationÂ thatÂ isÂ veryÂ strategicÂ andÂ haveÂ specialÂ authorityÂ inÂ theÂ healthÂ servicesÂ soÂ thatÂ theyÂ areÂ entitledÂ toÂ innovateÂ inÂ theÂ healthÂ service.Â UnitÂ costÂ calculationÂ purposesÂ ofÂ researchÂ compiledÂ byÂ theÂ PHCÂ UnitÂ CostÂ KonvensionalÂ MethodÂ andÂ ActivityÂ BasedÂ CostingÂ (ABC)Â Approach.Â TheÂ studyÂ wasÂ conductedÂ atÂ PHCÂ